A dissipative particle dynamics simulation study on phase diagrams for the self-assembly of amphiphilic hyperbranched multiarm copolymers in various solvents. Issue 36 (11th August 2017) - Tan, Haina; Yu, Chunyang; Lu, Zhongyuan; Zhou, Yongfeng; Yan, Deyue
Abstract : This work discloses for the first time the self-assembly phase diagrams of amphiphilic hyperbranched multiarm copolymers in various solvents by dissipative particle dynamics simulations. Abstract : Self-assembly of amphiphilic hyperbranched multiarm copolymers (HMCs) has shown great potential for preparing all kinds of delicate supramolecular structures in all scales and dimensions in solution. However, theoretical studies on the influencing factors for the self-assembly of HMCs have been greatly lagging behind. The phase diagram of HMCs in selective solvents is very necessary but has not been disclosed up to now. Here, the self-assembly of HMCs with different hydrophilic fractions in various solvents was studied systematically by using dissipative particle dynamics (DPD) simulations. Three morphological phase diagrams are constructed and a rich variety of morphologies, ranging from spherical micelles, worm-like micelles, membranes, vesicles, vesosomes, small micellar aggregates (SMAs), and aggregates of spherical and worm-like micelles to helical micelles, are obtained. In addition, both the self-assembly mechanisms and the dynamic processes for the formation of these self-assemblies have been systematically investigated. The simulation results are consistent with available experimental observations. Besides, several novel structures, like aggregates of spherical and worm-like micelles, vesosomes and helical micelles, are firstly discovered for HMC self-assembly. We believe the current work will extend the knowledge on the self-assembly of HMCs, especially on the control of supramolecular structures and on fabricating novel self-assemblies.